STUDENTS’ ENGAGEMENT IN VIRTUAL CREATIVE WRITING: DEVELOPING A CREATIVE WRITING STYLE - Surfaifel, Fety; Emilia, Emi; Gunawan, Wawan (English Review: Journal of English Education, 2023)
Writing is not a stand-alone mental activity; it is inextricably linked to other forms of creative design, such as drawing and music composition. Writing is a highly sought-after skill in today's digital world. Creative writing is defined as the fluent exchange of concepts in an original manner through the construction of logical connections between them in written form based on the individual's schema. This article discusses a study that examined factors affecting student engagement as a lens through which to examine students' perceptions of their creative writing class participation. These interactions emphasize the complexities of student engagement and promote the accuracy of the instruments and metrics used to study it. Cognitive engagement is concerned with a student's internal investment in the learning process, which includes inner psychological characteristics or nonvisible characteristics that encourage effort in acquiring, comprehending, and mastering the knowledge or skills required for academic work. As a result, English lessons were held for 12 students from Flores' private junior high school. They completed a questionnaire that included quantitative and qualitative questions. Descriptive statistics are used to examine qualitative data conceptually and statistically. The participants' experiences reflected various aspects of the students' participation. According to the findings, creative writing activities can help students learn about behavior, emotion, and cognition in a poetry class. However, in a poetry class, emotional involvement prevailed and was followed by behavioral engagement. Nonetheless, pupils maintained a low level of cognitive engagement.